2018
DOI: 10.3390/toxins10110445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Temperature on Native and Alien Nuisance Cyanobacteria from Temperate Lakes: An Experimental Approach

Abstract: In response to global warming, an increase in cyanobacterial blooms is expected. In this work, the response of two native species of Planktothrix agardhii and Aphanizomenon gracile, as well as the response of two species alien to Europe—Chrysosporum bergii and Sphaerospermopsis aphanizomenoides—to gradual temperature increase was tested. The northernmost point of alien species distribution in the European continent was recorded. The tested strains of native species were favoured at 20–28 °C. Alien species acte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 62 publications
(107 reference statements)
2
18
1
Order By: Relevance
“…Various environmental factors, such as water temperature, light and nutrient concentrations, influence MC synthesis indirectly through cellular growth [19,54]. In general, the toxicity of cyanobacterial blooms depends on the biomass of toxin producers [55,56] and the proportion of toxic genotypes in the population [45]. In our study, it has been confirmed that production of different MC isoforms, mainly derivatives of MC-RR and dmMC-LR, is a characteristic feature of Planktothrix subpopulations [17,56,57].…”
Section: Changes In Content Of Mcs In the Exposed P Agardhiisupporting
confidence: 73%
See 2 more Smart Citations
“…Various environmental factors, such as water temperature, light and nutrient concentrations, influence MC synthesis indirectly through cellular growth [19,54]. In general, the toxicity of cyanobacterial blooms depends on the biomass of toxin producers [55,56] and the proportion of toxic genotypes in the population [45]. In our study, it has been confirmed that production of different MC isoforms, mainly derivatives of MC-RR and dmMC-LR, is a characteristic feature of Planktothrix subpopulations [17,56,57].…”
Section: Changes In Content Of Mcs In the Exposed P Agardhiisupporting
confidence: 73%
“…In general, the toxicity of cyanobacterial blooms depends on the biomass of toxin producers [55,56] and the proportion of toxic genotypes in the population [45]. In our study, it has been confirmed that production of different MC isoforms, mainly derivatives of MC-RR and dmMC-LR, is a characteristic feature of Planktothrix subpopulations [17,56,57]. We also found changes in the contribution of particular MC isoforms to the cellular content of MCs produced by P. agardhii exposed to different concentrations of the extracts.…”
Section: Changes In Content Of Mcs In the Exposed P Agardhiimentioning
confidence: 99%
See 1 more Smart Citation
“…Its invasive character in colonizing new areas may gain from competitive advantages including nitrogen fixation, formation of resting stages and ecological plasticity, similarly to other invasive Nostocales cyanobacteria (Sukenik et al 2012). We note that although the impacts of the higher water temperatures related to climate change is still somewhat uncertain, the influence of water and air temperature should not be neglected in future studies as temperature effect has been shown to be an important driver regulating expansion of invasive cyanobacteria (Savadova et al 2018).…”
Section: Discussionmentioning
confidence: 88%
“…We note that although the impacts of the higher water temperatures related to climate change is still somewhat uncertain, the influence of water and air temperature should not be neglected in future studies as temperature effect has been shown to be an important driver regulating expansion of invasive cyanobacteria (Savadova et al . ).…”
Section: Discussionmentioning
confidence: 97%